Power electronics advanced conversion technologies - Luo, Fang Lin; Ye, Hong (CRC Press, Taylor & Francis Group, 2018)
Power Electronics is a large size technology, mainly covering four categories: the AC/DC rectifiers, DC/DC converters, DC/AC inverters, and AC/AC converters. This book offers approximately 100 novel topologies of all four. This new edition features an entirely new chapter on best switching angles to obtain lowest THD for multilevel DC/AC inverters. Additionally, all chapters have been updated and include homework problems throughout.